2019
DOI: 10.1002/smtd.201900325
|View full text |Cite
|
Sign up to set email alerts
|

Stable Li‐Metal Deposition via a 3D Nanodiamond Matrix with Ultrahigh Young's Modulus

Abstract: The practical usage of high‐energy lithium metal batteries remains a great challenge mainly due to the formation of uneven lithium deposition and huge volume fluctuation on the anode side, which increases the potential risks of a cell short‐circuit. Herein, a nanodiamond‐Li composite anode (ND‐Li) is created using a facile thermal infusion strategy, which can mechanically confine active Li‐metal in the ND matrix and minimize the electrode volume change during electrochemical cycling with high areal capacities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Hence, the crystal or surface structure of solid catalysts should be varied to not only enable the nucleation‐preferred formation of discharge products but also make the interaction between discharge products and catalyst surface appropriate. We believe that these rationales based on the growth dynamics of products from ORR/OER can be valid for a lot of solid catalysts and energy materials for future battery systems ranging from metals to oxides or hybrid materials …”
Section: Resultsmentioning
confidence: 91%
“…Hence, the crystal or surface structure of solid catalysts should be varied to not only enable the nucleation‐preferred formation of discharge products but also make the interaction between discharge products and catalyst surface appropriate. We believe that these rationales based on the growth dynamics of products from ORR/OER can be valid for a lot of solid catalysts and energy materials for future battery systems ranging from metals to oxides or hybrid materials …”
Section: Resultsmentioning
confidence: 91%
“…[7] Battery short-circuits induced by dendritic Li deposition can be relieved by employing functionalized separators, [8,9] artificial solid electrolyte interphases [10][11][12] and 3D composite anodes. [13][14][15] Li Coulombic efficiency (Li CE), defined as the ratio between the amount of Li stripped and Li plated at each cycle, is used as a truthful indicator to monitor the irreversible consumption of active Li. [16] Recently published works have demonstrated that low Li CE as a result of side reactions at the lithium metal surface and inefficient stripping process turns out to be the real culprit behind poor cyclability of practical full LMBs, but this issue is usually hidden when huge excess Li is used (e.g., thick Li metal anode > 300 µm).…”
Section: Doi: 101002/adma202001740mentioning
confidence: 99%
“…Extensive studies have explored to suppress dendritic lithium deposition by mechanical confinements (e.g., using functional separators, [ 7–9 ] rigid 3D hosts, [ 10 ] and solid‐state electrolytes [ 11–13 ] ), lithiophilic substrate modifications, [ 14 ] and electrolyte optimizations. [ 15–17 ] However, recent quantitative experiments demonstrated that low lithium Coulombic efficiency (Li CE) is the real culprit behinds the poor cyclability in practical LMBs with limited negative to positive capacity (N/P) ratio and electrolyte amount to cathode capacity (E/C) ratio.…”
Section: Introductionmentioning
confidence: 99%